2019
DOI: 10.1155/2019/5854315
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anticancer Properties and Mechanisms of Action of Formononetin

Abstract: Nature, a vast reservoir of pharmacologically active molecules, has been most promising source of drug leads for the cure of various pathological conditions. Formononetin is one of the bioactive isoflavones isolated from different plants mainly from Trifolium pratense, Glycine max, Sophora flavescens, Pycnanthus angolensis, and Astragalus membranaceus. Formononetin has been well-documented for its anti-inflammatory, anticancer, and antioxidant properties. Recently anticancer activity of formononetin is widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 89 publications
0
38
0
1
Order By: Relevance
“…Formononetin is an isoflavone from the Trifolium pretense (red clover plant) and Astragalus membranaceus (Huangqi) plants 56,242–244 . Formononetin belongs to a class of 7‐hydroisoflavones which have a substitution of methoxy group at Position 4 242–244 . Formononetin has been reported to exhibit anticancer effects by modulating several oncogenic signaling pathways, such as STAT3, MAPK, NF‐κB, and PI3K/Akt.…”
Section: Inhibition Of Stat3 Signalingmentioning
confidence: 99%
“…Formononetin is an isoflavone from the Trifolium pretense (red clover plant) and Astragalus membranaceus (Huangqi) plants 56,242–244 . Formononetin belongs to a class of 7‐hydroisoflavones which have a substitution of methoxy group at Position 4 242–244 . Formononetin has been reported to exhibit anticancer effects by modulating several oncogenic signaling pathways, such as STAT3, MAPK, NF‐κB, and PI3K/Akt.…”
Section: Inhibition Of Stat3 Signalingmentioning
confidence: 99%
“…Others show that Astragalus polysaccharides induced cell-cycle arrest in 4T1 cells (Park and Park 2018). Jiang et al (2019) reported the anti-cancer activity of formononetin as resulting from mechanisms involving halting metastasis, arresting cell cycle and inducing apoptosis, the IC 50 value of 1 µM for Formononetin against CNE2 (nasopharyngeal cell line) was reported. Wang and Ba (2015), analyzed the chemical composition of Astragali Radix ethanol extract using HPLC and NMR spectroscopy, and identified several compounds including (3R)-8,2'-dihydroxy-7,4'-dimethoxyisoflavan, 7,2'-dihydroxy-3',4'-dimethoxy-isoflavan-7,2'-dioxo-βd-glucoside, uridine, and astragaloside, which induced increase in the apoptosis rate of HepG2 cells, as evaluated by flow cytometry and MTT assay.…”
Section: Health-promoting Activities Of Astragalus (Astragalus Membranaceus) Based On In Vitro Studiesmentioning
confidence: 99%
“… 56 Flavonoids Kaempferol Kaempferia galanga Linn. 69 Formononetin Trifolium pratense ; Astragalus membranaceus 71 Extracts of bilberry fruits NA Vaccinium myrtillus L. 72 Quercetin Capparis spinosa L.; Piper Nigrum L. 73 Polyphenols Resveratrol Veratrum grandiflorum 74 Epigallocatechin-3-gallate Camellia sinensis (L.) O. Ktze. 75 Bergamot polyphenol fraction NA Citrus medica L. var.…”
Section: Effects Of Natural Products On T2dm-related Tissues Through Lipophagymentioning
confidence: 99%